Psychological resilience training for leaders in extreme times: study protocol of a randomized controlled trial - Hersom, Christina; Knoop, Hans Henrik; Justesen, Just Bendix (Frontiers in Psychology, 2025)
The fact that organizations face increasing complexity, crises and adverse events requires corporate leaders to respond rapidly and continuously while maintaining their wellbeing and high performance. Psychological resilience is crucial for navigating in extreme times. However, research on building resilience in leader contexts is scarce, particularly regarding how leaders learn to anticipate, cope with, and learn from crises and adversities. This protocol describes a randomized controlled study that examines the dynamics and impact of resilience training focusing both on self-leadership development (psychological resilience) for leading oneself and on leadership development for leading others (psychosocial resilience). Participants include formal leaders and key personnel responsible for leading organizational functions or units. The intervention group will receive resilience training, while the control group will be offered modified training post-intervention. The flexible intervention, grounded in applied positive psychology and cognitive interventions, will be longitudinal, incorporating experiential learning, and involving Human Management Resource (HRM) and educated Human Resource (HR) resilience trainers. Leaders will participate in 20 weekly and collective “resilience-sprints” during extreme times. Primary outcomes will be measured at three time points: before, during, and after the intervention to evaluate effects and explore resilience pathways. Continuous evaluations will identify the relevance of implemented resilience factors, and process evaluations will provide insights into contextual influences and dynamics of resilience building. The study integrates individual and organizational factors into a psychosocial resilience intervention designed as a comprehensive leader training program. The study protocol directs a study that aims to enhance empirical understanding of building leader resilience in extreme times of crisis and adversities, to benefit research in Management, HRM, and resilience fields. Ultimately, the study aim to help leaders face, cope, and adapt effectively by learning from experiences with the complexities of adverse and pressured organizational contexts.